Research Progress on Extraction Methods, Structure and Improvement of Chronic Diseases of Pectins - Jing SUN; Yubin WANG; Dan WANG; Wenting ZHAO; Xiaoyan ZHAO; Pan WANG (Shipin gongye ke-ji)
Pectin is a macromolecular water-soluble dietary fiber, which was widely distributed in fruits and vegetables. Pectin has various physiology functions, which has great development potential in the fields of food, medicine and health. By reviewing literature over the past 20 years, the common structures and extraction methods of pectin have been systematically summarized. Current structural studies of pectin have focused on homogalacturonans, rhamnogalacturonan-I and rhamnogalacturonan-II. Among the extraction methods, acid and aqueous extraction are the most mature technologies. Among these methods, subcritical aqueous extraction has great potential for application and popularization. Additionally, pectin plays an important role in ameliorating chronic metabolic diseases through intestinal microecology and other molecular pathways. Therefore, this article reviews the research progress in recent years on the structure, extraction methods, and the beneficial effect on the chronic diseases of pectin both domestically and internationally. Furthermore, this article summarizes the mechanism of action of pectin in improving chronic diseases and the conformational relationship between pectin structure and chronic diseases. This study would provide theoretical references for product development and industrial application of pectin.